Post-translational modifications of centromeric chromatin - García del Arco, Ana; Erhardt, Sylvia (Centromeres and Kinetochores, 2017)
Regulation of chromatin structures is important for the control of DNA processes such as gene expression, and misregulation of chromatin is implicated in diverse diseases. Covalent post-translational modifications of histones are a prominent way to regulate chromatin structure and different chromatin regions bear their specific signature of histone modifications. The composition of centromeric chromatin is significantly different from other chromatin structures and mainly defined by the presence of the histone H3-variant CENP-A. Here we summarize the composition of centromeric chromatin and what we know about its differential regulation by post-translational modifications.